2012
DOI: 10.1111/j.1365-2559.2012.04201.x
|View full text |Cite
|
Sign up to set email alerts
|

HER‐2/neu gene amplification in carcinoma ex pleomorphic adenoma in relation to progression and prognosis: a chromogenic in‐situ hybridization study

Abstract: These results suggest that HER2 may play an important role in the progression of CXPA, and that HER2 amplification may be an additional prognostic indicator of CXPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 35 publications
4
32
1
Order By: Relevance
“…One carcinoma with both genes amplified was metastatic, though the preceding benign tumour revealed no amplification of HER-2 nor c-myc oncogenes. Some researchers suggest that HER-2 plays a role in the progression of carcinoma ex PA, and that the presence of HER-2 amplification might be an indicator of poor prognosis, which is corroborated by the present study (34).…”
Section: Discussionsupporting
confidence: 79%
“…One carcinoma with both genes amplified was metastatic, though the preceding benign tumour revealed no amplification of HER-2 nor c-myc oncogenes. Some researchers suggest that HER-2 plays a role in the progression of carcinoma ex PA, and that the presence of HER-2 amplification might be an indicator of poor prognosis, which is corroborated by the present study (34).…”
Section: Discussionsupporting
confidence: 79%
“…Strong androgen receptor protein expression has been reported in 40% to 86% of salivary duct carcinoma cases, whereas HER2 protein overexpression and gene amplification have been reported in 17% to 44% and 12% to 52% of samples analyzed, respectively . Although the genomics of CEPA are less well defined, several studies have reported HER2 protein expression and gene amplification in CEPA at frequencies comparable to those seen in salivary duct carcinoma; HER2 overexpression has been suggested as a marker of malignant transformation of pleomorphic adenoma to CEPA . In both CEPA and salivary duct carcinoma, high concordance between HER2 amplification and strong protein expression has generally been reported .…”
Section: Discussionmentioning
confidence: 99%
“…Although the genomics of CEPA are less well defined, several studies have reported HER2 protein expression and gene amplification in CEPA at frequencies comparable to those seen in salivary duct carcinoma; HER2 overexpression has been suggested as a marker of malignant transformation of pleomorphic adenoma to CEPA . In both CEPA and salivary duct carcinoma, high concordance between HER2 amplification and strong protein expression has generally been reported . Among the subtypes of salivary gland cancer, HER2 overexpression has been identified most commonly in salivary duct carcinoma and CEPA, less frequently in adenocarcinoma NOS and mucoepidermoid carcinoma, and rarely in other subtypes, such as ACC .…”
Section: Discussionmentioning
confidence: 99%
“…The increasing frequency of HER2 gene amplification increases with CXPA progression, suggesting that HER2 may play a key role in the progression of this tumor [17]. HER2 , which encodes the 185-kDa transmembrane glycoprotein with tyrosine kinase activity, is considered to play an important role in controlling cell growth and development.…”
Section: Discussionmentioning
confidence: 99%